2021
DOI: 10.1038/s41598-021-85857-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impacts of glucocorticoid treatment in patients with polymyalgia rheumatica and giant cell arteritis

Abstract: Identifying comorbidities in polymyalgia rheumatica/giant cell arteritis (PMR/GCA) is crucial for patients’ outcomes. The present study aimed to evaluate the impact of the inflammatory process and glucocorticoid treatment on aortic arterial stiffness and body composition in PMR/GCA. 77 patients with newly diagnosed PMR/GCA were treated with oral glucocorticoids and followed for 40 weeks. Aortic pulse wave velocity (PWV) was measured at baseline and during the follow-up period and compared to the results of tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Therefore, initially, we expected an association between inflammatory markers and the emergence of glucocorticoid adverse effects ( 33 ). Similarly, other studies have demonstrated that aortic PWV decreases and aortic PWV is correlated with the percentage change in plasma CRP in patients with GCA and PMR under glucocorticoid therapy ( 34 , 35 ). Hafner et al ( 36 ) reported that glucocorticoid administration in patients with GCA had been associated with a reduction of carotid IMT.…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, initially, we expected an association between inflammatory markers and the emergence of glucocorticoid adverse effects ( 33 ). Similarly, other studies have demonstrated that aortic PWV decreases and aortic PWV is correlated with the percentage change in plasma CRP in patients with GCA and PMR under glucocorticoid therapy ( 34 , 35 ). Hafner et al ( 36 ) reported that glucocorticoid administration in patients with GCA had been associated with a reduction of carotid IMT.…”
Section: Discussionsupporting
confidence: 53%
“…Our results included nine studies with 2600 patients diagnosed with GCA, most of which 1853 (71.3%) were females. Seven studies were conducted in France [ 15 - 21 ], three in the United States of America (USA) [ 22 - 24 ], one in Austria [ 25 ], and one in Denmark [ 26 ]. Nine of the included studies were retrospective [ 15 - 17 , 19 - 21 , 23 , 25 , 26 ], one was prospective [ 24 ], one was a case-control [ 18 ], and one was cross-sectional [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…Serious complications, including aortic aneurysms or dissection, might result from aortitis in GCA [ 15 , 20 ]. Risk of bias assessment showed high risk in two studies [ 17 , 20 ], moderate risk in seven studies [ 15 , 16 , 18 , 22 , 24 - 26 ], and unclear risk in three studies [ 19 , 21 , 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…Despite being anti-inflammatory and immunosuppressive drugs, their use is restrained by the fear of the occurrence of adverse effects (AEs). The therapeutic effects of GCs range from pain relief and disease-modifying effects in arthritides, such as rheumatoid arthritis (RA), to strong immunosuppressive actions in systemic autoimmune diseases such as systemic lupus erythematosus (SLE) or vasculitides [2,4,5].…”
Section: Introductionmentioning
confidence: 99%